Mitigation of mercury contamination through the acceleration of vegetation succession - WIWIK EKYASTUTI; ENY FARIDAH; SUMARDI SUMARDI; YADI SETIADI (Society for Indonesian Biodiversity, 2016)
Ekyastuti W, Faridah E, Sumardi, Setiadi Y. 2016. Mitigation of mercury contamination through the acceleration of vegetation succession. Biodiversitas 17: 84-89. The success of the restoration of the tailings ex-gold mining through the succession is highly dependent on the ability of plants to grow and adapt to the troubled land. Restoration through natural succession takes a very long time. Therefore, human intervention is required to accelerate the succession. The purpose of this research was to improve the effectiveness of mitigation of mercury contamination through the acceleration of vegetation succession. This research has been carried out in a greenhouse using an experiment with a completely randomized design. There are 8 treatment consists of four indigenous species (Dillenia excelsa, Melastoma affine, Cinnamomum porrectum and Casuarina junghuhniana) grown alone (one species) and collective (more than one species) in the tailing media with a mercury content of 20 ppm. The results showed that the planting collectively have a mutually supportive interaction, so that increased the plant growth. In addition, collective planting two or four different species of plants, and the D. excelsa itself could decrease the concentration of mercury in the tailing. The acceleration of vegetation succession through the right choice of plants species and planting collectively, capable to increasing the potential of mitigation of mercury contamination in the tailings.